2006
DOI: 10.1111/j.1600-6143.2006.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Islets Transplanted Intraportally into the Liver are Stimulated to Insulin and Glucagon Release Exclusively through the Hepatic Artery

Abstract: Not much is known about the physiology of intraportally transplanted islets. One reason for this is that it is difficult to study such islets, since they are scattered throughout the liver. We employed a perfusion technique to characterize the functional properties of syngeneic intrahepatic 1-month-old islet grafts, and compared them to islets transplanted beneath the kidney capsule, as well as native islets. The cellular composition of the islet grafts was also examined. Glucose and arginine administered thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
4
20
1
Order By: Relevance
“…The argument that insulin would be delivered more physiologically after intraportal transplantation has received little support in the literature. It has clearly been demonstrated in experimental studies that intraportally transplanted islets respond to glucose stimulation only when perfused via the hepatic artery; no response is observed after challenge via the portal vein [19]. Similar findings come from the area of tumour biology (cf.…”
Section: Revisiting the Rationale For Selecting The Intraportal Routesupporting
confidence: 69%
See 1 more Smart Citation
“…The argument that insulin would be delivered more physiologically after intraportal transplantation has received little support in the literature. It has clearly been demonstrated in experimental studies that intraportally transplanted islets respond to glucose stimulation only when perfused via the hepatic artery; no response is observed after challenge via the portal vein [19]. Similar findings come from the area of tumour biology (cf.…”
Section: Revisiting the Rationale For Selecting The Intraportal Routesupporting
confidence: 69%
“…During this process the islet becomes incorporated in the vessel wall and may eventually receive blood supply from the vas vasorum demonstrated that transplanted islets respond with proliferation and improved engraftment when exposed to growth factors released during liver regeneration [16,17]. By this process, the islets become incorporated in the newly formed liver parenchyma and induce revascularisation from the hepatic artery [18,19] within the first week after transplantation (cf. tumour cells actively penetrating the portal venous wall).…”
Section: Revascularisation Of Intraportally Transplanted Isletsmentioning
confidence: 99%
“…We chose the renal subcapsular site to enable us to perform the in vivo studies. However, considering that islets implanted intraportally in the liver are located downstream of the pancreas, any factors released from the gland would be expected to reach such transplanted islets at even higher concentrations, at least prior to islet revascularisation [39]. We therefore deem the results obtained in the present study as pertinent to intraportally transplanted islets.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, we recently observed that islets implanted into the kidney and the liver both have a decreased first phase of insulin release in response to glucose as compared with native islets [39]. This impaired insulin release in control islet grafts may reflect disturbances in the secretory machinery of beta cells [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…While adequate revascularisation is crucial for islet survival after transplantation, the vascular density in revascularised transplanted islets is markedly decreased [31]. In addition, previous data have demonstrated that the first phase of glucose-stimulated insulin release from islets transplanted to the liver was delayed, and less prominent when compared to that from the pancreas [32]. Considering islet function after transplantation, the decrease in islet vascular structure might be a main cause of decreased beta cell function.…”
Section: Discussionmentioning
confidence: 99%